Relationship between household food insecurity and minimum dietary diversity among pregnant women attending antenatal care at public health facilities in Fiche town, Oromia region, Central Ethiopia: A facility-based cross-sectional study - Misra Abdulahi; Tadese Bulto Lemi; Gali Nega Ababor (BMJ Open)
Background Pregnant women experiencing food insecurity often compromise the quality of their nutrition by consuming a monotonous diet. Food insecurity and dietary monotony, defined as lack of variety in one’s diet, are two importan vt factors that cause undernutrition. Different studies focused on the factors associated with minimum dietary diversity, and there is limited evidence regarding the relationship between minimum dietary diversity and household food insecurity. Therefore, this study aims to assess the relationship between household food insecurity and minimum dietary diversity among pregnant women at health facilities in Fiche town.Objective To determine whether there was a relationship between the household food insecurity and minimum dietary diversity among pregnant women in Fiche town health facilities in Oromia region, Central Ethiopia.Design A facility-based cross-sectional study was conducted in September 2022, involving 422 pregnant women.Setting The study was conducted in Fiche town, located in the North Showa Zone of Oromia region in Ethiopia. The town is home to one specialised hospital and two health centres.Methods A structured questionnaire administered by an interviewer was used to collect data. Data were gathered using KoboToolbox V.2022.2.0 and analysed with SPSS V.23. A χ2 test and binary logistic regression analyses were employed to examine the relationship between household food insecurity and minimum dietary diversity (defined as consuming at least 5 out of 10 specified food groups in the previous day or night). Bivariable and multivariable logistic regression analyses were conducted to identify the predictors of minimum maternal dietary diversity.Results The study found that only 34.6% of the participants met the minimum dietary diversity criteria. A significant relationship was identified between household food insecurity and minimum dietary diversity, χ2 (2, n=32.43, p value=0.001). The variables that were found to be significant included being severely food-insecure (adjusted OR (AOR)=4.25, 95% CI: 1.26 to 14.38), having a history of illness in the last 2 weeks prior to assessment (AOR=2.14, 95% CI: 1.04 to 4.57) and lacking nutritional counselling during antenatal care (ANC) follow-up (AOR=9.24, 95% CI: 4.92 to 17.36). These factors were found to be significantly associated with both household food insecurity and minimum dietary diversity.Conclusion The study underscores the importance of addressing household food insecurity and enhancing dietary diversity among pregnant women. It recommends interventions such as improving access to nutritious food, providing support during illness and offering comprehensive nutritional counselling during ANC visits.